Model-based methodology for implementing MARTE in embedded real-time software - Mohd. Zaki, Mohd. Zulkifli (IEEE, 2011)
This paper presents an integration of a model-based methodology for embedded real-time software with MARTE. However, although has being introduced as a new profile to overcome problem in previous profile, a sound and systematic methodology is necessary to tackle complexity problem that arise. The objective of this paper is to propose an integration of profile and method for satisfying embedded real-time software requirements and helping engineers to model their system, enhancing the structure and behavior modeling. For that, this paper describes a proposed methodology for the integration process, involving two elements: a profile and a method. The integration result will support to solve complexity whereby the profile is used to solve the lack of specific modeling language notation for embedded real-time system and the method can provide a systematical software process. The proposed integration component model is applied on a case study to show its enhancements.